Visual integration of Historic Cities Centers - Al-Askary, Abdul Hussien Abd Ali; Al-kaissi, Atheer Omran Hayyawi (Iraqi Journal of Architecture and Planning, 2016)
Historic centers are considered as one of the main problems introduced in the contemporary literatures, The concept of visual integration was discussed in several studies on several levels (philosophical, urban, architectural), while they did not get to intensively within the studies dealing with the concept on a holistic level and in all its aspects . The research problem defind as, "The lack of image about the concept and indicators of street visual integration " The hypothesis of Search is "Vary the effect of the elements , relationships and properties visual for elevations at the level of the Part and the whole contribute to the visual integration " The main objective of this research "to find the most important elements, relationships and properties visual affecting as Indicators measurable and verification components to contribute to the visual integration of townscape" It was necessary for study to explain some of the basic concepts such as the concept of urban integration ØŒhistoric cities centers access to the concept of visual integration, as well as the study of properties and relations visual for townscape .